Visualização Volumétrica Aplicada às Geociências - IESCHECK, ANDREA LOPES; SLUTER, CLAUDIA ROBBI; DEDECEK, RENATO ANTÔNIO (Pesquisas em Geociências, 2008)
This paper is on volume visualization of spatial data. It aims at showing new possibilities to visualize three-dimensional phenomena such as geology, soils, geophysics, seismic and the like. The use of volumes in the evaluation processes allows one to visualize and to explore the phenomenon as a continuous body in space, thus incorporating the third dimension in cartography. The volumetric visualization is a branch of scientific visualization that has shown a fast growth and its goal is to comprehend the internal structure and the behavior of three-dimensional volumetric objects. Volumetric visualization depends on the interaction. We must, therefore, interact with the volume trough rotations, cuts and other forms of graphic manipulation, seeking the complete information. The methodology of this research entails the acquisition of three-dimensional data, three-dimensional interpolation, as well as volume formation and visualization by means of three-dimensional Geographic Information System and volumetric visualization software. Soil’s data were interpolated in order to be continuously represented in three-dimensional space. The outcome of volume representations of physical and chemical properties is a new way to visualize the soil and a new source of knowledge to the study of this phenomenon.